“PNP slows down” – linearly-reduced whole body joint velocities and altered gait patterns in polyneuropathy - Walz, Isabelle D.; Waibel, Sarah; Lippi, Vittorio; Kammermeier, Stefan; Gollhofer, Albert; Maurer, Christoph (Frontiers in Human Neuroscience, 2023)
Introduction Gait disturbances are a common consequence of polyneuropathy (PNP) and a major factor in patients’ reduced quality of life. Less is known about the underlying mechanisms of PNP-related altered motor behavior and its distribution across the body. We aimed to capture whole body movements in PNP during a clinically relevant mobility test, i.e., the Timed Up and Go (TUG). We hypothesize that joint velocity profiles across the entire body would enable a deeper understanding of PNP-related movement alterations. This may yield insights into motor control mechanisms responsible for altered gait in PNP. Methods 20 PNP patients (61 ± 14 years) and a matched healthy control group (CG, 60 ± 15 years) performed TUG at (i) preferred and (ii) fast movement speed, and (iii) while counting backward (dual-task). We recorded TUG duration (s) and extracted gait-related parameters [step time (s), step length (cm), and width (cm)] during the walking sequences of TUG and calculated center of mass (COM) velocity [represents gait speed (cm/s)] and joint velocities (cm/s) (ankles, knees, hips, shoulders, elbows, wrists) with respect to body coordinates during walking; we then derived mean joint velocities and ratios between groups. Results Across all TUG conditions, PNP patients moved significantly slower (TUG time, gait speed) with prolonged step time and shorter steps compared to CG. Velocity profiles depend significantly on group designation, TUG condition, and joint. Correlation analysis revealed that joint velocities and gait speed are closely interrelated in individual subjects, with a 0.87 mean velocity ratio between groups. Discussion We confirmed a PNP-related slowed gait pattern. Interestingly, joint velocities in the rest of the body measured in body coordinates were in a linear relationship to each other and to COM velocity in space coordinates, despite PNP. Across the whole body, PNP patients reduce, on average, their joint velocities with a factor of 0.87 compared to CG and thus maintain movement patterns in terms of velocity distributions across joints similarly to healthy individuals. This down-scaling of mean absolute joint velocities may be the main source for the altered motor behavior of PNP patients during gait and is due to the poorer quality of their somatosensory information. Clinical Trial Registration https://drks.de/search/de, identifier DRKS00016999.